Answer:
18
Step-by-step explanation:
24 divided by 12 is 2. 36 divided by 2 is 18.
Hope this is right.
Answer:
Length of third side is: ![\mathbf{8m^3-4m^2+3m}](https://tex.z-dn.net/?f=%5Cmathbf%7B8m%5E3-4m%5E2%2B3m%7D)
Step-by-step explanation:
Perimeter of triangle = ![18m^3+2m^2-m](https://tex.z-dn.net/?f=18m%5E3%2B2m%5E2-m)
Length of side 1= ![5m^3+3m^2-2m](https://tex.z-dn.net/?f=5m%5E3%2B3m%5E2-2m)
Length of side 2= ![5m^3+3m^2-2m](https://tex.z-dn.net/?f=5m%5E3%2B3m%5E2-2m)
We need to find length of third side.
The formula used is: ![Perimeter \:of\:triangle=Sum\:of\:all\:sides](https://tex.z-dn.net/?f=Perimeter%20%5C%3Aof%5C%3Atriangle%3DSum%5C%3Aof%5C%3Aall%5C%3Asides)
Putting values and finding length of third side.
![Perimeter \:of\:triangle=Sum\:of\:all\:sides\\18m^3+2m^2-m=5m^3+3m^2-2m+5m^3+3m^2-2m+Length\:of\:3rd\:side\\18m^3+2m^2-m=5m^3+5m^3+3m^2+3m^2-2m-2m+Length\:of\:3rd\:side\\18m^3+2m^2-m=10m^3+6m^2-4m+Length\:of\:3rd\:side\\Length\:of\:3rd\:side=18m^3+2m^2-m-(10m^3+6m^2-4m)\\Length\:of\:3rd\:side=18m^3+2m^2-m-10m^3-6m^2+4m\\Length\:of\:3rd\:side=18m^3-10m^3+2m^2-6m^2-m+4m\\Length\:of\:3rd\:side=8m^3-4m^2+3m](https://tex.z-dn.net/?f=Perimeter%20%5C%3Aof%5C%3Atriangle%3DSum%5C%3Aof%5C%3Aall%5C%3Asides%5C%5C18m%5E3%2B2m%5E2-m%3D5m%5E3%2B3m%5E2-2m%2B5m%5E3%2B3m%5E2-2m%2BLength%5C%3Aof%5C%3A3rd%5C%3Aside%5C%5C18m%5E3%2B2m%5E2-m%3D5m%5E3%2B5m%5E3%2B3m%5E2%2B3m%5E2-2m-2m%2BLength%5C%3Aof%5C%3A3rd%5C%3Aside%5C%5C18m%5E3%2B2m%5E2-m%3D10m%5E3%2B6m%5E2-4m%2BLength%5C%3Aof%5C%3A3rd%5C%3Aside%5C%5CLength%5C%3Aof%5C%3A3rd%5C%3Aside%3D18m%5E3%2B2m%5E2-m-%2810m%5E3%2B6m%5E2-4m%29%5C%5CLength%5C%3Aof%5C%3A3rd%5C%3Aside%3D18m%5E3%2B2m%5E2-m-10m%5E3-6m%5E2%2B4m%5C%5CLength%5C%3Aof%5C%3A3rd%5C%3Aside%3D18m%5E3-10m%5E3%2B2m%5E2-6m%5E2-m%2B4m%5C%5CLength%5C%3Aof%5C%3A3rd%5C%3Aside%3D8m%5E3-4m%5E2%2B3m)
So, Length of third side is: ![\mathbf{8m^3-4m^2+3m}](https://tex.z-dn.net/?f=%5Cmathbf%7B8m%5E3-4m%5E2%2B3m%7D)
Answer:
The radius is approximately 2 93
from both sides of the equation.
Answer:
Apply the distributive property.
6 ⋅ 5 + 6 (-3x) = -4 x - 12
Multiply
6 by 5 . 30 + 6 (-3 x) = - 4 x - 12
Multiply
− 3 by 6 . 30 - 18 x = - 4 x - 12
Add
4 x to both sides of the equation.
30 - 18 x + 4 x = - 12
Add
− 18 x and 4 x . 30 - 14 x = - 12
Subtract
30
from both sides of the equation.
- 14 x = - 12 - 30
Subtract
30 from
− 12 . - 14 x = - 42
x = 3
Step-by-step explanation: